Development of Augmented Reality-Based Interactive Learning Environment for Enhancing Learning Outcomes of Fifth-Grade Students on Indonesian Cultural Diversity - Sari, Novita Wulan; Aeni, Kurotul (FKIP Universitas Lampung, 2025)
Development of Interactive Learning Environment Based on Augmented Reality to Improve Learning Outcomes of Grade V Students on the Material of Indonesian Cultural Diversity. Purpose: This study was aimed at creating an interactive learning environment by utilizing Augmented Reality (AR) technology to boost the enthusiasm and learning outcomes of fifth grade students of SDN Pagendisan, Pati Regency, on the subject of Pancasila Education, specifically on the theme of Indonesian Cultural Diversity. Methods: This study used a Research and Development (R&D) approach, using the ADDIE (Analysis, Design, Development, Implementation, Evaluation) model to develop. Findings: The developed learning tools include AR-integrated flashcards that contain 3D elements such as traditional houses, traditional clothing, and regional music. Evaluation based on material experts and media experts showed high media suitability, with an average feasibility score of 89.5. The pilot test conducted with 28 grade 5 primary school students showed a significant improvement in terms of motivation and learning outcomes. Statistical analysis using t-test indicated a significant difference between pretest and posttest scores (p<0.05), with an average increase in learning outcomes of 0.75 based on the n-Gain test. Conclusion: This study concludes that AR-based learning tools are effective in improving student motivation and learning outcomes, cultivating more dynamic and interesting learning experiences. Keywords: augmented reality, learning outcomes, motivation, pancasila education.